The changing meaning of left and right: supply- and demand-side effects on the perception of party positions - Heiko Giebler; Thomas M. Meyer; Markus Wagner (Journal of Elections, Public Opinion and Parties, 2021)
Political conflict is often described in terms of “left” and “right” even though societal conflicts stem from various sub-dimensions such as economic and cultural issues. We argue that individuals map parties' left-right positions based on party positions on such underlying dimensions, though their impact depends on their importance for parties and citizens. To test this, we study the German Alternative für Deutschland (AfD) whose programmatic appeal has changed fundamentally in the last years, as have citizens' issue concerns. Using longitudinal data from the German Longitudinal Election Study (GLES), we find that citizens' perceptions of the AfD's left-right position are more closely related to the party's position on specific issues (1) when these issues are prominent in the party's communication and (2) for citizens that care more about these issues. Moreover, how voters perceive left and right in comparison to parties' issue emphasis also affects vote choice. Our findings have important implications for the meaning of left and right, electoral behaviour, representation, and party competition.
Keywords: 330